A naturalistic, long-term follow-up of purging disorder. Issue 6 (15th April 2021) - Forney, K. Jean; Crosby, Ross D.; Brown, Tiffany A.; Klein, Kelly M.; Keel, Pamela K.
Abstract: Background: The DSM-5 introduced purging disorder (PD) as an other specified feeding or eating disorder characterized by recurrent purging in the absence of binge eating. The current study sought to describe the long-term outcome of PD and to examine predictors of outcome. Methods: Women ( N = 84) who met research criteria for PD completed a comprehensive battery of baseline interview and questionnaire assessments. At an average of 10.24 (3.81) years follow-up, available records indicated all women were living, and over 95% were successfully located ( n = 80) while over two-thirds ( n = 58) completed follow-up assessments. Eating disorder status, full recovery status, and level of eating pathology were examined as outcomes. Severity and comorbidity indicators were tested as predictors of outcome. Results: Although women experienced a clinically significant reduction in global eating pathology, 58% continued to meet criteria for a DSM-5 eating disorder at follow-up. Only 30% met established criteria for a full recovery. Women reported significant decreases in purging frequency, weight and shape concerns, and cognitive restraint, but did not report significant decreases in depressive and anxiety symptoms. Quality of life was impaired in the physical, psychological, and social domains. More severe weight and shape concerns at baseline predicted meeting criteria for an eating disorder at follow-up. Other baseline severity indicators and comorbidity did not predict the outcome. Conclusions: Results highlight the severity and chronicity of PD as a clinically significant eating disorder. Future work should examine maintenance factors to better adapt treatments for PD.